2018
DOI: 10.1016/j.nrjag.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of structural and electrical properties of ZnO varistor samples doped with different additives

Abstract: Three samples of ZnO doped with CuO as additive were prepared by solid state reaction from the calcined oxides and characterized by SEM, EDX, and AFM. The results revealed the presence of intergranular phase. Additives found to be between ZnO grains. The conductivity of the three samples was measured with the frequency up to 100 KHz by LCR circuit. The calculated coefficients of nonlinearity and the conductivity are shown to be highly dependent on the frequency, concentration of copper oxide, surface morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The oxidation process is very effective to convert a conducting SPS samples to varistor characteristic performance with a higher nonlinearity (52). This indicates the diffusion of oxygen into grain boundaries to form thick grain boundary junctions as explained in the literature . The insufficient oxygen diffusion in the dense MOV compacts also explains the appearance of high leakage current at low voltages.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The oxidation process is very effective to convert a conducting SPS samples to varistor characteristic performance with a higher nonlinearity (52). This indicates the diffusion of oxygen into grain boundaries to form thick grain boundary junctions as explained in the literature . The insufficient oxygen diffusion in the dense MOV compacts also explains the appearance of high leakage current at low voltages.…”
Section: Resultsmentioning
confidence: 52%
“…This indicates the diffusion of oxygen into grain boundaries to form thick grain boundary junctions as explained in the literature. [16][17][18]30 The insufficient oxygen diffusion in the dense MOV compacts also explains the appearance of high leakage current at low voltages. In order to reach thorough and uniform oxygen diffusion, some MOV samples were only partially compacted using SPS technique, and a subsequent sintering in air was carried out.…”
Section: Electrical Propertymentioning
confidence: 99%
“…The densities of the ZnO nanorods were 107 µm − 2 , 94 µm − 2 , 72 µm − 2 , and 65 µm − 2 when the synthesis time was 10 min, 20 min, 30 min, and 60 min, respectively. The measured heights and diameters, as well as the calculated densities, of the ZnO nanorods were used to determine the total surface area (S, nm 2 ), the total volume (V, nm 3 ), and the S/V ratio; the results are shown in Table 2 as a function of synthesis time. As the synthesis time increased from 10 min to 60 min, the total surface area increased from 1.01 ⋅ 10 6 to 3.04 ⋅ 10 7 nm 2 , the total volume increased from 1.03 ⋅ 10 7 to 8.32 ⋅ 10 8 nm 3 , and the S/V ratio decreased from 9.79 ⋅ 10 − 2 to 3.65 ⋅ 10 − 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The measured heights and diameters, as well as the calculated densities, of the ZnO nanorods were used to determine the total surface area (S, nm 2 ), the total volume (V, nm 3 ), and the S/V ratio; the results are shown in Table 2 as a function of synthesis time. As the synthesis time increased from 10 min to 60 min, the total surface area increased from 1.01 ⋅ 10 6 to 3.04 ⋅ 10 7 nm 2 , the total volume increased from 1.03 ⋅ 10 7 to 8.32 ⋅ 10 8 nm 3 , and the S/V ratio decreased from 9.79 ⋅ 10 − 2 to 3.65 ⋅ 10 − 2 . These results showed that it was possible to manipulate the height, diameter, and aspect ratio of the ZnO nanorods by controlling the synthesis time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation